UMPH donates 1,000 face shield and drinking water to the healthcare workers - UMP, PNC (2020)
Concerned with the struggle faced by the frontliners and healthcare workers to combat the spread of Covid-19 virus, especially in Pahang State, UMP Holdings Sdn. Bhd (UMPH), a subsidiary of Universiti Malaysia Pahang (UMP), helps produced 1,000 face shields and donated 720 bottles of drinking water to the healthcare workers.